Land sparing is crucial for urban ecosystem services. Issue 7 (1st September 2015) - Stott, Iain; Soga, Masashi; Inger, Richard; Gaston, Kevin J
Abstract : The world's cities must grow to accommodate an increasing urban population, and achieving this with minimal impact on ecosystem structures and functions is a major challenge. At opposite ends of a possible development spectrum are "land sharing" – extensive sprawling urbanization where built land and natural space are interspersed – and "land sparing" – intensive and extremely compact urbanization alongside separate, large, contiguous green space. Using case studies across urbanization gradients, we demonstrate that land sparing is crucial for sustaining a majority of ecosystem services. Conversely, some land sharing may also be necessary to ensure that people benefit from urban green space. Future urban development should carefully consider green space provision, to maximize the services provided by urban ecosystems. This can be achieved by optimizing distributions of development intensity across cities by means of top‐down, policy‐led approaches.